Factors associated with overweight/obesity of children aged 6-12 years in Indonesia - Sofi Oktaviani; Mayumi Mizutani; Ritsuko Nishide; Susumu Tanimura (BMC, 2023)
Abstract Background Globally, the prevalence of childhood obesity has increased considerably, including in Indonesia. Obesity results from multifactorial interactions at the personal, familial, and environmental levels. However, little is known about the factors associated with overweight/obesity among children in Indonesia. This study is intended to identify personal, familial, and environmental factors associated with overweight/obesity in children aged 6-12 years in Indonesia. Methods Study design was a secondary data analysis using the Indonesia Family Life Survey in 2014/2015, focusing on 6,090 children aged 6-12 years. The questions covered the child's body mass index and potential personal, familial, and environmental factors. Logistic regression analysis was performed to identify the personal, familial, and environmental factors. Results The mean age of participants was 8.9 years (SD = 2.0); 51.0% were boys; 9.4% were overweight; and 8.1% were obese. Overweight and obesity were associated with age [AOR 1.09 (95% CI 1.04-1.14)], having an overweight [AOR 1.93 (95% CI 1.58-2.36)] or obese [AOR 3.36 (95% CI 2.43-4.61)] father compared with a normal father, being of Chinese [AOR 9.51 (95% CI 1.43-79.43)] or Javanese [AOR 1.60 (95% CI 1.16-2.24)] ethnicity compared with Sundanese ethnicity, and residing in an urban area [AOR 1.36 (95% CI 1.10-1.70)]. A lower risk of child overweight/obesity was associated with the father's perception [AOR 0.56 (95% CI 0.38-0.80)] and mother's perception [AOR 0.66 (95% CI 0.43-0.98)] of the child's food consumption as being less than adequate compared with adequate. Conclusions Risk factors in children for overweight/obesity were older age, having an overweight/obese father, membership of certain ethnic groups, and urban residence. The main protective factor was parents' perception that a child's food consumption was less than adequate. Health promotion programs focused on these factors could help control or prevent childhood obesity in Indonesia.